Italian protocol for massive solar integration: From solar imbalance regulation to firm 24/365 solar generation. (May 2021) - Pierro, Marco; Perez, Richard; Perez, Marc; Prina, Matteo Giacomo; Moser, David; Cornaro, Cristina
Abstract: This work describes a progressive strategy to achieve 100% penetration of intermittent renewables at minimal cost. The strategy works to optimally transform variable renewable energy (RE) into firm, effectively dispatchable generation. This functional dispatchability enables large-scale displacement of conventional generation at equal or lower production cost. By way of this strategy, we delineate a pathway for a full renewable energy transition of the Italian electric mix. In order to achieve 100% renewables in any grid, the fundamental imbalance between the supply of the resource and demand must be alleviated. We propose a transition that starts by addressing net load forecast imbalances resulting from renewables' prediction errors and ends with the transformation of intermittent renewables into firm, effectively dispatchable generation sources. Highlights: A strategy to achieve 100% penetration of renewables at minimal cost is developed. Flexible PV plants are proactively curtailed in tandem with cost-optimized batteries. We delineate a pathway for a full renewable energy transition of Italian electric mix.